THE INFLUENCE OF ANESTHESIA ON PROLONGATION OF QTC INTERVAL IN PATIENTS THAT UNDERWENT AN OPEN-HEART SURGERY - Borzanovic, Sanja M; Babic, Rade (Medicinski podmladak, 2020)
Introduction: Prolongation of QTc interval may cause cardiac electrical instability resulting in polymorphic ventricular tachycardia if the “torsades de pointes” type, as well as ventricular fibrillation and sudden death. It is known that anesthetics, laryngoscopy and tracheal intubation have various influences on QTc duration. Material and methods: Study enrolled 100 consecutive patients that underwent an open-heart surgery at a single cardiosurgical center. Standard institutional protocols for premedication, introduction and conduction of anesthesia were used. Correction of QT interval was calculated according to Bazzet’s formula. For the assessments of the influence of premedications, anesthetics, operation type and tracheal intubation and extubation on QTc interval we focused to taking ECG at the following time points: baseline, after premedication, immediate postoperatively at admission to the intensive care unit, before extubation, immediately following extubation and a final following transfer to the general ward. As cut-off value of QTc prolongation we applied values >450 ms for men and >470 ms for women. Results: Out of 100 successive patients, 55 had postoperative prolongation of QTc. In this group, males were prevalent (81,8%) in comparison to the group with normal QTc interval (64,4%; p= 0, 049); average glycemic index was higher (7, 6 mmol/l) in comparison to the group with normal QTc interval (6, 5 mmol/l; p= 0, 021) and average value of serum potassium was higher (4, 5 mmol/l) in comparison to the group with normal QTc (4, 1 mmol/l; p= 0, 003). Conclusion: We confirmed prolongation of QTc interval during open-heart surgery, associated with anesthesia, operative and perioperative factors related to tracheal intubation and/or extubation and the increased sympathetic activity and catocholamine release. Amiodarone therapy, as well as increased perioperative glucose and potassium levels were associated with QTc prolongation. Key words: QTc interval, anesthesia, open-heart surgery.
Keywords: Premedication; Intubation; QTc interval; anesthesia; open-heart surgery.